2002
DOI: 10.1159/000063881
|View full text |Cite
|
Sign up to set email alerts
|

Green Tea <i>(Camellia sinensis)</i> Protects against Selenite-Induced Oxidative Stress in Experimental Cataractogenesis

Abstract: Cataract is the leading cause of blindness worldwide. It is a multifactorial disease primarily associated with oxidative stress produced by free radicals. The protection offered by various antioxidants in cataract development is well established. Polyphenolic compounds present in green tea (Camellia sinensis) are reported to possess antioxidant property in various pathological conditions. The present study was undertaken to evaluate the anticataract potential of green tea leaf (GTL) extract in the development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 24 publications
0
33
0
Order By: Relevance
“…Antioxidant vitamins and green tea decrease lens crystallin-bound fluorescence. Previous data revealed that diabetes increased crystallin-bound fluorescence attributable to glycoxidation (12) or dihydropyridinium cross-links (26) and that green tea ameliorated selenite cataract in the rat (27). Here, crystallin-bound fluorescence at 370/440 nm was higher in water-soluble fraction (Fig.…”
Section: Resultsmentioning
confidence: 55%
“…Antioxidant vitamins and green tea decrease lens crystallin-bound fluorescence. Previous data revealed that diabetes increased crystallin-bound fluorescence attributable to glycoxidation (12) or dihydropyridinium cross-links (26) and that green tea ameliorated selenite cataract in the rat (27). Here, crystallin-bound fluorescence at 370/440 nm was higher in water-soluble fraction (Fig.…”
Section: Resultsmentioning
confidence: 55%
“…23,24 It is known that selenite induces a significant depletion of GSH and increases membrane damage as indicated by the levels of MDA. 25 We observed that grape seed proanthocyanidin (IH636) extract prevented cataract development in at least half the eyes and reduced the amount of opacity in the rest. This effect was associated with higher GSH levels and lower MDA concentrations.…”
Section: Discussionmentioning
confidence: 90%
“…Of sodium selenite, 100 μM was chosen for the present study as this dose as reported by Gupta et al [27] and Kinoshita [28]. Exposure of the rat lenses to the above substances in primary culture had a damaging effect on cell morphology and its overall antioxidant status.…”
Section: Discussionmentioning
confidence: 99%